Pipeline embolization for an iatrogenic intracranial internal carotid artery pseudoaneurysm after transsphenoidal pituitary tumor surgery: Case report and review of the literature. Issue 1 (February 2020) - Nariai, Yasuhiko; Kawamura, Yosuke; Takigawa, Tomoji; Hyodo, Akio; Suzuki, Kensuke
Intracranial pseudoaneurysms are uncommon and among the most difficult lesions to treat with surgery or endovascular means without parent artery sacrifice. Here, we report on a patient who underwent successful treatment using a flow-diverting stent for an iatrogenic intracranial internal carotid artery pseudoaneurysm following a vessel injury after endoscopic pituitary tumor resection via the transsphenoidal approach. A 62-year-old man with a Rathke's cleft cyst presenting with bitemporal hemianopia and progressive decline of left visual acuity underwent endoscopic transsphenoidal pituitary tumor resection. During dura incision, brisk arterial bleeding was encountered from the right internal carotid artery. Immediate packing was performed, and hemostasis was achieved. Three days after the vessel injury, an angiography revealed a pseudoaneurysm (2.9 × 2.1 mm) at the cavernous segment of the right internal carotid artery, which showed enlargement on follow-up magnetic resonance imaging at six days postoperatively. Pipeline embolization was performed nine days after the vessel injury. Angiography performed one month after Pipeline embolization revealed significant stagnation but not complete occlusion of blood flow inside the pseudoaneurysm cavity. Dual antiplatelet therapy was replaced with single antiplatelet therapy. Follow-up angiograms three months after Pipeline embolization confirmed complete obliteration of the pseudoaneurysm and successful endoluminal reconstruction of the damaged vessel. Despite the possibility of short-term bleeding and the need for dual antiplatelet therapy administration for a certain period, the use of flow-diverting stents is a feasible vessel-sparing option in the management of intracranial internal carotid artery pseudoaneurysms resulting from transsphenoidal surgery injuries if intraoperative hemodynamic stability can be achieved with effective packing.